Familial Mediterranean fever without fever as a cause of monoarthritis. (4th July 2013) - Mattiassich, Georg; Semlitsch, Georg; Nadler, Karin; Rainer, Franz
Abstract : Familial Mediterranean fever (FMF) is an autosomal recessive hereditary disease. FMF-related arthritis affects large joints, especially in the lower extremities. It starts with acute pain and swelling and affects one joint at a time. Fever is the most common symptom in FMF. Monoarthritis as the sole symptom is relatively rare and thus delayed diagnosis of the disease in a patient who had been suffering from monoarthritis for several years. Genetic analysis showing typical mutations in the patient eventually resulted in correct diagnosis, although classical clinical diagnostic criteria were not met. The patient received appropriate therapy with colchicine, which led to remission of the symptoms.